Hydrogen and syngas production by superadiabatic combustion – A review. (1st July 2016) - Abdul Mujeebu, Muhammad
Highlights: A review on application of superadiabatic combustion for H2 and syngas production. Conversions of hydrocarbon fuels including biomass and hydrogen sulfide are focused. It covers non-catalytic TPOX, HFC, hybrid PM-catalyst reactor and SAC without PM. Separate sections deal the numerical modeling trends and the R&D challenges ahead. There is wide scope for further research on SAC reactors with and without PM. Abstract: The application of superadiabatic combustion (SAC) technology for hydrogen and syngas production has been a focus of intensive research in the recent past. A lot of researches have been reported on the conversion of various gaseous and liquid hydrocarbon fuels, hydrogen sulfide and biomass into hydrogen or syngas, by using SAC. The porous medium combustion has been recognized as the most feasible technique to realize SAC, and few recent studies reported to have achieved SAC even without a porous medium (PM). This article compiles the works done so far in this area and suggests future directions. Following the general background, the history of hydrogen/syngas production by SAC is provided. Further developments are organized in the subsequent sections, which include all the published works on SAC-based hydrogen production from hydrocarbon fuels, hydrogen sulfide and biomass. The works on hybrid PM-catalyst filtration combustion and numerical modeling of SAC-based hydrogen/syngas production are discussed in separate sections. Subsequently, the development of SAC reactor without PM is presented, followed by summary and conclusion. This review reveals that there is a wide scope for future research particularly on hybrid-filtration combustion, biomass gasification, hybrid PM-Catalyst reactors, SAC reactors without PM, and on development of efficient reformers for practical stationary and portable applications. Scope is also open for detailed characterizations, both experimental and numerical, with various PM materials and structures and with variety of fuels under realistic operating conditions.